2015
DOI: 10.4049/jimmunol.1402172
|View full text |Cite
|
Sign up to set email alerts
|

Heme Exporter FLVCR Is Required for T Cell Development and Peripheral Survival

Abstract: All aerobic cells and organisms must synthesize heme from the amino acid glycine and the tricarboxylic acid (TCA) cycle intermediate succinyl Coenzyme A for incorporation into hemoproteins such as the cytochromes needed for oxidative phosphorylation. Most studies on heme regulation have been done in erythroid cells or hepatocytes; however much less is known about heme metabolism in other cell types. The feline leukemia virus subgroup C receptor (FLVCR) is a 12 transmembrane domain surface protein that exports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Because lck-cre + mice differ from WT mice, care should also be taken when interpreting results using only an lck-cre + control. Intriguingly, some investigators reported no differences between lck-cre + or lck-cre 2 mice, whereas others did (17,19,21,(29)(30)(31)(32)(33)(35)(36)(37) (Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
“…Because lck-cre + mice differ from WT mice, care should also be taken when interpreting results using only an lck-cre + control. Intriguingly, some investigators reported no differences between lck-cre + or lck-cre 2 mice, whereas others did (17,19,21,(29)(30)(31)(32)(33)(35)(36)(37) (Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
“…As a result, heme-containing proteins play crucial roles in all cells (Sawicki et al, 2015); however, heme can also play lineage-specific roles in differentiation (Philip et al, 2015). Proper heme levels are also crucial for normal fetal development, as defects can lead to limb deformities in addition to abnormal erythropoiesis (Keel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…179 Recent reports suggest that FLVCR is also critical in T cell development and survival. 180 While these effects may validate that excess heme is toxic, it may also speak to the necessity of heme secretory pathways in cell and tissue development and ultimately innate immune functionality. Does heme serve a purpose when released from cells, much like HMGB1 and other mediators including cytokines/chemokines or even growth factors?…”
Section: Heme and Ho-1-derived Products: The Balance Between Cell Injmentioning
confidence: 99%